Critical emancipatory reflection on establishing an equal, trusting relationship among surgery participants in clinical practice in China - Lai Yan-Ling (Sciendo, 2019)
Reflection is considered to be one of the important ways to learn from one's experience, and one should be encouraged to apply the skill of reflection in lifelong learning. The author used the critical emancipatory reflection theory to reflect on a practice issue, which was related to the relationship between doctors and nurses, and tries to become a lifelong reflective practitioner in clinical work.